THE ROLE OF THE TEACHER IN DEVELOPING STUDENTS' INTEREST IN LEARNING (Web of Technology: Multidimensional Research Journal, 2024)
The article presents proposals for organizing work on career guidance in general education schools, the theoretical foundations of career guidance and a creative approach to it, and professional culture.